2019
DOI: 10.1192/bjo.2019.82
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal violence and mental health outcomes following disaster

Abstract: Background Disasters pose a documented risk to mental health, with a range of peri- and post-disaster factors (both pre-existing and disaster-precipitated) linked to adverse outcomes. Among these, increasing empirical attention is being paid to the relation between disasters and violence. Aims This study examined self-reported experiences of assault or violence victimisation among communities affected by high, medium, and low disaster severity following the 2009 bushfires in Victoria, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 33 publications
4
73
0
Order By: Relevance
“…The number of women seeking assistance from domestic violence services increased during the Australian bushfires and current COVID-19 pandemic, and the Federal Government has responded with substantial funding for the sector. The elevated prevalence of domestic violence associated with the Australian disasters is consistent with national and international evidence that violence against women increases after major disasters, including fires, floods, hurricanes or pandemics (Enarson and Chakrabarti, 2009;Molyneaux et al, 2020). Women's status is shaped by social and health inequalities including practices and policies that privilege male roles, perspectives and experiences.…”
supporting
confidence: 59%
“…The number of women seeking assistance from domestic violence services increased during the Australian bushfires and current COVID-19 pandemic, and the Federal Government has responded with substantial funding for the sector. The elevated prevalence of domestic violence associated with the Australian disasters is consistent with national and international evidence that violence against women increases after major disasters, including fires, floods, hurricanes or pandemics (Enarson and Chakrabarti, 2009;Molyneaux et al, 2020). Women's status is shaped by social and health inequalities including practices and policies that privilege male roles, perspectives and experiences.…”
supporting
confidence: 59%
“…Studies focusing on the impact of humanitarian crises and natural disasters on domestic violence have shown that the stress associated with these emergencies leads to an increase in VAWC (Molyneaux et al, 2019 ; Rubenstein, Lu, MacFarlane, & Stark, 2020 ; Seddighi, Salmani, Javadi, & Seddighi, 2019 ). In the current context of the COVID-19 pandemic, the confinement measures may have amplified this increased risk of VAWC.…”
Section: Why Has the Covid-19 Pandemic Led To An Increase In Domesticmentioning
confidence: 99%
“…It is unknown what effect the combination of these risks may have on the population of parents. However, each of these factors have an evidence-base demonstrating potential risks to adult and child mental health and wellbeing (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). There is evidence showing increased risks of mental health problems, drug and alcohol use, and family violence during and after crisis events and disasters (5)(6)(7)17).…”
Section: Introductionmentioning
confidence: 99%
“…However, each of these factors have an evidence-base demonstrating potential risks to adult and child mental health and wellbeing (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). There is evidence showing increased risks of mental health problems, drug and alcohol use, and family violence during and after crisis events and disasters (5)(6)(7)17). Job loss, employment uncertainty, and difficulties in juggling work and family roles are associated with increases in parent mental health problems, couple conflict, and child mental health problems (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%